A new finite element procedure for simulation of flexural fatigue behaviours of hybrid engineered cementitious composite beams. (15th October 2022) - Zhu, Shiyao; Zhang, Y.X.; Lee, C.K.
Graphical abstract: Highlights: Development of a material damage model for ECC under fatigue loading. Calibration of material damage model parameters for ECC under fatigue loading. Development of a simplified FE procedure for ECC beams under fatigue loading. Validation of the proposed simplified FE analysis procedure with test results. Abstract: This study proposes a new finite element (FE) analysis procedure for simulation of flexural fatigue behaviours of hybrid fibre reinforced engineered cementitious composite (hybrid ECC) beams. The proposed method simplifies the analysis of hybrid ECC beams under fatigue loading, which could have fatigue life up to millions of cycles, into a small number of static FE analyses corresponding to a set of designated load cycles with equivalent fatigue damages. An ECC material damage model is first developed to describe the degrading of material properties caused by fatigue loading. This material damage model defines the relationships of two critical damage properties of ECC, namely the degraded stiffness and the accumulated plastic strain with the number of load cycles applied. By using the developed material damage model, a simplified analysis procedure is then proposed for the fatigue analysis of hybrid ECC beams under bending. The accuracy and reliability of the proposed material damage model and analysis procedure are validated by comparing experimental results obtained from bending tests of three types of hybrid ECC beams under three different stress ranges with the modelling predictions. It is found that the proposed material damage model and analysis procedure provided good predictions of the fatigue responses of the hybrid ECC beams in terms of material damages, deformation and fatigue life.